Trends in the Development of Youth Social Activities: Ethical Aspect - Oltmisheva Nasibakhon Gulomjonovna (Genius Journals, 2022)
This article provides information about the role of national and spiritual values in the formation of social activity of the youth of our country, the formation of its moral culture, moral consciousness and psyche.
Keywords: Youth, moral culture; moral consciousness; social activity; mass culture